Implementasi Program Roots dalam Meminimalisir Perilaku Bullying di SMPN 35 Makassar - Abidin, Pebrianti; Saprin, Saprin; Afif, Ahmad (Universitas Cokroaminoto Palopo, 2025)
Bullying remains a significant issue in educational settings, affecting students' psychological well-being and academic performance. SMPN 35 Makassar implemented the Roots Program, which focuses on minimizing bullying through peer influence and student-led advocacy. This study aims to analyze the planning, implementation, challenges, and outcomes of the Roots Program at SMPN 35 Makassar using a qualitative descriptive approach. The research involved semi-structured interviews, observations, and document analysis with key stakeholders, including the school principal, counseling teachers, facilitator teachers, and Student Agents of Change. The findings reveal that the planning phase was well-structured, supported by the school’s designation as a Sekolah Penggerak and financial aid from UNICEF, which provided essential digital facilities. However, the selection of facilitators from social studies (IPS) teachers instead of counseling teachers (BK) raised concerns about their expertise in handling bullying-related issues. Despite this, facilitators demonstrated competence through prior training. During implementation, the program adhered to the Roots Program guidelines, consisting of 15 training sessions for Student Agents of Change, culminating in Roots Day, an anti-bullying awareness event involving the entire school community. The initiative successfully raised awareness, promoted peer support, and fostered a positive school environment. However, challenges included a lack of facilitator continuity, absence of an annual regeneration system for Student Agents of Change, and insufficient monitoring and evaluation mechanisms. The study concludes that while the Roots Program significantly enhanced anti-bullying awareness, its long-term sustainability remains uncertain. The school should involve more counseling teachers as facilitators, establish an annual recruitment system for Student Agents of Change, and implement structured monitoring and evaluation. Additionally, integrating digital and social media campaigns could further amplify the program’s impact. The Roots Program can achieve long-term sustainability and contribute to a safer, bullying-free school environment.